The practice and poetics of fieldwork: Hugh Cott and the study of camouflage - Forsyth, Isla (Elsevier, 2014)
This paper examines the practice and poetics of the British zoologist Hugh Cott’s fieldwork in order to explore the hybrid nature of developments in biological and military camouflage. Specifically focusing on two fieldtrips conducted in the 1920s to the Amazon and the Zambesi, and by examining how Cott communicated his scientific findings through photography and art this paper reveals that the performance of scientific knowledge production is spatially contingent; born of embodied, creative and demanding experiences and through multiple human and nonhuman engagements. Finally, it examines how this knowledge was transferred and utilised to develop mid-twentieth military camouflage. Thus, this paper considers how the craft and aesthetics of fieldwork shapes how nature is observed, recorded and communicated as scientific knowledge and military technology.